On simplification of first line partial derivatives equation system solution - Jurgaitis, Donatas (Lietuvos matematikos rinkinys, 2001)
In this paper it has been analyzed first line partial derivatives system, the line of which strongly degenerates. Transformation has been determined, which simplifies the system, i.e., the main matrix of a new system coefficients distinguish characteristics, that all matrix elements over or under main diagonal (except one) asymptotically equal zero.